2020
DOI: 10.1039/d0ta04644b
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of n-type half-Heusler NbCoSn with heavy-element Pt substitution

Abstract: Half-Heusler compounds with a valence electron count of 18, including ZrNiSn, ZrCoSb, and NbFeSb, are good thermoelec-tric materials owing to favorable electronic structures. Previous computational studies had predicted a high...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 53 publications
5
46
4
Order By: Relevance
“…giving N v = 6, which appears to be partially responsible for m DoS * = 6.1 m e in the NbCoSn 1-x Sb x series (Table 1). 197,198 At present the largest zT is found for X-site alloying between Nb and Ta, yielding zT 1000 K = 0.75 for Nb 0.4 Ta 0.6 CoSn 0.94 Sb 0.06 . 196 Better low temperature performance has been observed when using Pt as both n-type dopant and phonon scatterer in NbCo 0.95 Pt 0.05 Sn, due to the large mass difference between Co and Pt.…”
Section: Other Hh Phasesmentioning
confidence: 82%
See 1 more Smart Citation
“…giving N v = 6, which appears to be partially responsible for m DoS * = 6.1 m e in the NbCoSn 1-x Sb x series (Table 1). 197,198 At present the largest zT is found for X-site alloying between Nb and Ta, yielding zT 1000 K = 0.75 for Nb 0.4 Ta 0.6 CoSn 0.94 Sb 0.06 . 196 Better low temperature performance has been observed when using Pt as both n-type dopant and phonon scatterer in NbCo 0.95 Pt 0.05 Sn, due to the large mass difference between Co and Pt.…”
Section: Other Hh Phasesmentioning
confidence: 82%
“…One recent HH family which has emerged is the X V CoSn (X V = Nb and Ta) phases, which are intrinsically n-type materials. 187,[196][197][198] The bandstructure of NbCoSn appears contain a doubly degenerate X-point conduction band minimum,…”
Section: Other Hh Phasesmentioning
confidence: 99%
“…This discrepancy is manifested in terms of the theoretical prediction of some of the undoped n-type narrow band gap half-Heusler alloys as p-type semiconductor. For instance, the ab initio electronic band structure calculations performed within the density functional theory (DFT) framework predicted NbCoSn to be a p-type semiconductor [39], while experimental measurements found the alloy to be intrinsically n-type [40][41][42]. Similarly, the Seebeck coefficient measurements for ZrNiSn and HfNiSn [43][44][45] confirmed these alloys to be n-type semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…The valence electrons in these alloys occupy all bonding electronic states, while antibonding states remain unoccupied thereby leading to the semiconducting band gap. Examples of thermoelectric materials belonging to this class of alloys include X NiSn and X CoSb (where X = Hf, Zr, Ti) [31][32][33][34][35][36][37] and NbCoSn-based alloys [38][39][40][41]. All the above mentioned half-Heusler alloys with a valence electron count of 18 are promising candidates for thermoelectric applications with large Seebeck coefficient of up to several hundred μV K −1 and moderate electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…This approach yields zT enhancement for a variety of materials including (V/Nb/Ta)FeSb, [ 11,21–24 ] (Ti/Zr/Hf)Co(Sb/Bi), [ 25–31 ] (Ti/Zr/Hf)Ni(Sn,Pb), [ 12,26,32,33 ] and (Nb/Ta)CoSn. [ 34–36 ] Recently, we reported that point‐defect scattering has been the major phonon scattering mechanism of half‐Heusler compounds other than the intrinsic phonon–phonon interaction, whereas scattering from other defects is less pronounced. [ 18 ] The insufficient contributions from the higher‐dimension defects (such as 2D grain boundaries) greatly attenuated the scattering intensity of phonons, especially at lower frequencies that carry the most heat.…”
Section: Introductionmentioning
confidence: 99%